Annihilation operators associated with unstable vacua in non-equilibrium thermo-field dynamics - Yoshida, K.; Arimitsu, T. (Condensed Matter Physics, 2008)
Out of thermal equilibrium state, the vacuum is unstable and evolves in time. Consequently, the annihilation
operators associated with the unstable vacuum depend on time. This dissipative time-evolution of quantum
systems can be systematically treated, within the canonical operator formalism referred to as non-equilibrium
thermo-field dynamics. Given is an alternative route to derive the time-dependent annihilation operators within
the formalism. As an example, time-dependent annihilation operators for the systems of bosonic and fermionic
semi-free fields are derived. Далеко вiд стану термiчної рiвноваги вакуум є нестабiльним i змiнюється з часом. В результатi, оператори анiгiляцiї, пов’язанi з нестабiльним вакуумом, еволюцiонують з часом. Ця дисипативна часова еволюцiя квантових систем може бути систематично дослiджена в рамках формалiзму канонiчного оператора, який має назву нерiвноважна термо-польова динамiка. В рамках цього формалiзму запропоновано альтернативний шлях отримання залежних вiд часу операторiв анiгiляцiї. Як приклад, отримано залежнi вiд часу оператори анiгiляцiї для систем бозонних i фермiонних напiввiльних полiв.